The Development of Sustainable Industrial Economic Growth on the Potential of Rhizome Plants for the Aromatherapy Industry: A Study of Empirical, Scientific and Halal Aspects - Nusran, Muhammad; Amin, Asni; Abdullah; Mail, Abdul; Nur, Taufik (International Journal of Integrative Sciences, 2024)
The development of rhizome plants as raw materials for traditional medicine in South Sulawesi has not been widely developed, compared to other regions such as Java. In South Sulawesi, lemongrass, jeringau, betel, and ginger plants have not been managed professionally, especially when associated with the Petik Olah Jual (PELAJU) concept. This study aims to examine and determine the development of the industrial economy through cultivation and picking and selling of rhizome plants (Jeringau, Lemongrass, and Betel) as raw materials for traditional medicine / aromatherapy production at the farm level and also to analyze the application of the Petik Olah Jual concept to the potential of the green economy in processing rhizome plant extracts as raw materials for traditional medicines in the Makassar, Gowa, Maros and Takalar (Mamminasata) region. Conclusion: the mapping of rhizome plants in South Sulawesi and efforts to empower the Industrial economy and the welfare and skills of rhizome farmers to process into halal-based traditional medicine products are quite prospective. Economic development of the rhizome plant industry as a raw material for traditional medicine production at the farm level is used as a raw material for traditional medicine, can increase farmers' income